Financial structure and stability: An empirical exploration - Shikha Singh; Mandira Sarma (Journal of Central Banking Theory and Practice, 2020)
This paper attempts to investigate empirically whether financial and macroeconomic stability of economies are significantly affected by the structure of their financial systems, viz., bank-based and market-based structures. Using panel data estimations based on data from 82 countries for the period of 1996-2012, we find that in general, bank-based financial system contributes significantly to instability of the financial sectors and currency market. We also find some evidence that within the bank-based structure, higher presence of foreign banks is positively associated with currency market pressure. Additionally, the results show that the choice of bank-based versus market-based financial structure is important for low income countries. Banks in low income countries contribute to exchange market pressures whereas stock markets leads to reduction in such pressure. In high income countries, stock markets do not significantly affect banking and currency market instability.
Keywords: G0; G21; G10; 330; Financial structure; bank-based financial system; market-based financial system; stability